Initial testing (stage 1) of the phosphatidylinositol 3′ kinase inhibitor, SAR245408 (XL147) by the pediatric preclinical testing program1. Issue 5 (21st September 2012) - Reynolds, C. Patrick; Kang, Min H.; Carol, Hernan; Lock, Richard; Gorlick, Richard; Kolb, E. Anders; Kurmasheva, Raushan T.; Keir, Stephen T.; Maris, John M.; Billups, Catherine A.; Houghton, Peter J.; Smith, Malcolm A.
Abstract Background Activation of the PI3 kinase pathway occurs frequently in many adult cancers and is implicated in tumor cell proliferation, survival, and resistance to chemotherapy and radiotherapy. However, less is known regarding the relevance of this pathway in pediatric cancers. Here we have evaluated SAR245408, a novel small molecule PI3K inhibitor, against childhood cancer cell lines and xenografts. Procedures SAR245408 was tested against the PPTP in vitro cell line panel at concentrations from 10 to 100 µM and against the PPTP in vivo xenograft panels at a dose of 100 mg/kg administered orally daily × 14. Results In vitro SAR245408 demonstrated cytotoxic activity, with a median relative IC50 value of 10.9 µM (range 2.7–24.5 µM). SAR245408 was well tolerated in vivo, and all 44 tested xenograft models were evaluable for efficacy. SAR245408 induced significant differences in EFS distribution compared to control in 29 of 37 (79%) of solid tumor xenografts and in two of seven (29%) ALL xenografts. SAR245408 induced tumor growth inhibition meeting criteria for intermediate EFS T/C activity (EFS T/C > 2) in 4 of 37 (11%) solid tumor xenografts. Intermediate EFS T/C activity was also observed for two of seven (29%) evaluable ALL xenografts. Objective responses were not observed for solid tumor or for ALL xenografts. Conclusions Under the conditions evaluated in this study, SAR245408 achieved modest single‐agent activity against most PPTP preclinical models. Further exploration of SAR245408 in combination with standard agents or with other signaling inhibitors could be considered. Pediatr Blood Cancer 2013; 60: 791–798. © 2012 Wiley Periodicals, Inc.